Comparative study between peripherally and centrally acting sublethal and lethal doses of Leiurus quinquestriatus scorpion venom in rabbits: The usefulness of the sodium channel blocker lidocaine - Fatani, Amal J. (2010)
BACKGROUND: Scorpion envenomation is common among desert dwellers, affecting several systems and resulting in multiple organ dysfunction (MOD) or failure (MOF), mainly due to their action on Na(+) channels. Although scorpion venoms toxins do not pass the blood brain barrier, their CNS effects are prominent, occurring in conjunction with, or as an aftermath of peripheral actions of the venom. OBJECTIVE: To determine the ability of venom of the common scorpion Leiurus quinquestriatus (LQQ) to induce MOD or MOF when injected into rabbits in micro quantities centrally (intracerebroventricularly, i.c.v.) or macro amounts peripherally (s.c. or i.v.). Also, to assess if the Na(+) channel blocker lidocaine can protect rabbits from the resultant manifestations. METHODS: Rabbits were injected with LQQ venom centrally or peripherally, in either sublethal or lethal doses, and MOD or MOF determined by assessing: cardiac output (CO), estimated hepatic blood flow (EHBF), biochemical parameters indicative of cardiac/hepatic/renal and pancreatic functions, blood pressure (BP), survival, lung/body index (LBI, indicative of pulmonary edema), and/or histological changes in hearts, lungs, livers plus kidneys. In pre-treatment experiments, lidocaine was injected 40 min before venom and protective ability examined. RESULTS: LQQ venom in sublethal doses caused comparable significant reductions (vs control) in CO and EHBF when injected i.c.v. (2 μg kg(−1)) or s.c. (0.2 mg kg(−1)). Both routes caused gradual dose-related enhanced levels of creatine kinase, lactate dehydrogenase, aspartate aminotransferase, alanine aminotransferase, creatinine, glucose and amylase, indicating MOD. Also, characteristic venom-induced changes in BP were evident after lethal doses of venom i.v. (0.5 mg kg(−1)) or i.c.v. (3 μg kg(−1)). Histological changes in the organs plus LBI were comparable after i.c.v. and i.v. venom injection, with animals ultimately exhibiting MOF. Lidocaine (1 mg kg(−1) i.v., then infusion 50 μg kg(−1) min(−1), 30 min before venom), protected the animals from MOF evoked by lethal doses of the venom (whether injected centrally or peripherally), as evidenced by the amelioration of the venom’s effects on blood pressure, LBI, survival and multiple organ histopathological manifestations. CONCLUSION: LQQ venom, whether injected centrally or peripherally caused comparable systemic dose-dependent MOD or MOF, with the latter attenuated by the Na(+) channel blocker lidocaine, indicating a role for Na(+) channels.